ECOLOGY AS AN OBJECT OF LINGUISTIC RESEARCH (Conferencea, 2022)
This article discusses the stages of the formation of ecological vocabulary and terminology, the integration of various scientific areas in ecology. The article gives a detailed description of such terms as "environmental education", "environmental thinking" and "ecological outlook".